Hadith #2565 - Sunan Abi Dawud - Abdullah ibn Ja'far; Asim al-Ahwal عاصم الأحول; Ibrahim bin Muhammad bin al-Harith إبراهيم بن محمد أبو اسحاق الفزاري; Muwarraq bin Mashmarij al-Ajli مورق بن المشمرج العجلي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) was present with a she-mule which he rode, so Ali said: If we made asses cover mares we would have animals of this type. The Messenger of Allah (ﷺ) said: Only those who do not know do that.
Grade: Sahih

Hadith #5159 - Sunan Abi Dawud - Abu Dharr al-Ghaffari; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Mujahid bin Jabir مجاهد بن جبر; Muwarraq bin Mashmarij al-Ajli مورق بن المشمرج العجلي (Sunan Abi Dawud)
when I was beating a servant of mine, I heard a voice behind me saying: know, Abu Mas’ud-Ibn al-Muthanna said: “twice”-that Allah has more power over you than you have over him. I turned round and saw that it was that it was the prophet (May peace be upon him). I said : Messenger of Allah! He is free for Allah’s sake. He said : If you had not done it, fire would have burned you or the fire would have touched you.
Grade: Sahih